2021
DOI: 10.1093/plphys/kiab013
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism for brassinosteroids suppressing climacteric fruit ripening

Abstract: The plant hormone ethylene is important for the ripening of climacteric fruit, such as pear (Pyrus ussuriensis), and the brassinosteroid (BR) class of phytohormones affects ethylene biosynthesis during ripening via an unknown molecular mechanism. Here, we observed that exogenous BR treatment suppressed ethylene production and delayed fruit ripening, whereas treatment with a BR biosynthesis inhibitor promoted ethylene production and accelerated fruit ripening in pear, suggesting BR is a ripening suppressor. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Brassinosteroids (BRs) are important steroid hormones that promote plant growth and development, for example, cell proliferation, pollen development, fruit ripening, and senescence [52]. The latest study showed that endogenous BRs, including typhasterol (TY), 6-deoxocastasterone (6-deoxoCS), and castasterone (CS), reduced gradually during pear (Pyrus ussuriensis) fruit development [6]. The progressive reduction of endogenous BRs during fruit development indicated that BRs might be an inhibitory factor of fruit ripening.…”
Section: Brassinosteroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brassinosteroids (BRs) are important steroid hormones that promote plant growth and development, for example, cell proliferation, pollen development, fruit ripening, and senescence [52]. The latest study showed that endogenous BRs, including typhasterol (TY), 6-deoxocastasterone (6-deoxoCS), and castasterone (CS), reduced gradually during pear (Pyrus ussuriensis) fruit development [6]. The progressive reduction of endogenous BRs during fruit development indicated that BRs might be an inhibitory factor of fruit ripening.…”
Section: Brassinosteroidsmentioning
confidence: 99%
“…The application of 3 µM epibrassinolide (EBR) observably suppressed ethylene production and effectively maintained fruit firmness during the apple-fruit storage period. In contrast, a treatment of 10 µM brassinazole (Brz), an inhibitor of BR biosynthesis, evidently promoted ethylene production and decreased fruit firmness in apples [6]. In pears, exogenous EBR and Brz treatment has the same effect as in apples [6].…”
Section: Brassinosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment of tomato with the BR synthetic inhibitor brassinazole inhibited the expression of ethylene synthesis related genes and ethylene production [113] . In pear (P. ussuriensis), treatment of fruit with epibrassinolide (EBR), a brassinosteroid, significantly inhibited ethylene production and maintained fruit firmness compared with untreated control fruit during storage [114] .…”
Section: Brassinosteroidsmentioning
confidence: 99%
“…Ji et al reported that endogenous BRs such as typhasterol (TY), 6-deoxocastasterone (6-deoxoCS) and castasterone (CS) gradually decreased during pear (P. ussuriensis) fruit development (Fig. 2), and treatment with 0.2, 3 or 10 µmol•L −1 EBR significantly inhibited ethylene production and well-maintained fruit firmness compared with untreated control fruit [114] . They further revealed that high concentrations of BRs activate the expression of TF PuBZR1, PuBZR1 suppresses the enzyme activity of PuACO1 by direct protein interaction in the cytoplasm, and the transcription of PuACO1 and PuACS1a in the nucleus, thereby reducing ethylene production and suppressing fruit ripening.…”
Section: Brassinosteroidsmentioning
confidence: 99%